AN EVALUATION OF TURBINE AND GENERATOR PERFORMANCE AT PT INALUM POWER PLANT USING GADS, EXPONENTIAL DISTRIBUTION FMEA ANALYSIS - Uun Novalia Harahap; Nurul Atikah (Sean Institute, 2022)
PT INALUM Power Plant is a company that operates a hydropower plant consisting of the Siguragura (SGP) and Tangga (TNP) power stations. So that requires it to continue to optimize its maintenance policy. Even though maintenance activities have been carried out, the frequency of damage to each unit still occurs frequently. As a result, the unit trips (experiencing termination), namely forced outage, which affects the amount of downtime. To overcome this problem, in this study the method used to determine the performance of the power plant is the Generating Availability Data System (GADS), then to determine the reliability and rate of failure using an exponential distribution. Meanwhile, to repair damage to turbines & generators using FMEA analysis. MTR bushings were repaired routinely for 51.306 hours (±2 days) or 102.612 hours (±4 days). 46% and in the Ladder Hydroelectric Power Plant it occurred in the T/Ge3 unit of 2.80%. The appropriate evaluation action is to carry out maintenance with the type of periodic maintenance and preventive maintenance. Particularly T/Ge1 PLTA Siguragura on the air cooler & metal cooling tube component and T/Ge3 PLTA Tangga on the MTR Bushing component. The right maintenance strategy to minimize forced outage is to review planned maintenance on the air cooler & metal cooling tube for routine flushing for 35,287 hours (±1 day) or 70,574 hours (±3 days).